Effects of participation in and connectedness to the LGBT community on substance use involvement of sexual minority young people. (June 2018) - Demant, Daniel; Hides, Leanne; White, Katherine M.; Kavanagh, David J.
Abstract: Introduction: Research shows disproportionate levels of substance use among sexual minority young people. A range of reasons for these disparities have been suggested, including connectedness to and participation in the LGBT community. Little is known about how these constructs are related to substance use involvement in sexual minority (sub)groups or how these relationships are affected by other factors. Methods: 1266 young sexual minority Australians completed a cross-sectional online survey. Multiple regressions were conducted to assess associations between connectedness to and participation in the LGBT community on substance use involvement, before and after controlling for other factors such as substance use motives, psychological distress, wellbeing, resilience, minority stress, and age. Results/conclusion: Most participants identified as homosexual (57%, n = 726) and male (54%, n = 683). In the overall sample, participation in and connectedness the LGBT community were significantly associated with increased substance use involvement before (F(2, 1263) = 35.930, p ≤ 0.001, R 2  = 0.052) and after controlling for other variables (F(8, 1095) = 33.538, p ≤ 0.001, R 2  = 0.191), with meaningfully higher effect sizes for participation than for connectedness. After controlling for other variables, connectedness only remained significant for homosexuals. Effect sizes for participation were higher for females than males, and bisexuals than homosexuals. However, participation in the LGBT Community was not associated with substance use in participants identifying with a non-binary gender identity. In conclusion, substance use involvement was associated with participation in the LGBT community, but connectedness to the LGBT community only had a weak association with substance use involvement in the homosexual subgroup. Highlights: LGBT community participation is associated with increased substance use involvement. Effects of LGBT community participation on substance use highest on bisexuals and males. LGBT community connectedness and substance use associated only in homosexuals.